Analisis Efisiensi Fire Pump 717-P-3 Emergency Water Pump Jetty 1 (Marine) PT. Pertamina (Persero) RUII Production Sungai Pakning - Abdurrahman, Ridwan; Ilhan, Muhammad Rifky (Fakultas Teknik UMRI, 2024)
This research was carried out in the industrial world. This aims to enable students to understand field conditions in the world of work, apply the knowledge gained in college, increase their knowledge and improve their ability to deal with problems that occur. This report contains the author's special activities and topics during practical work activities at PT. Pertamina (Persero) RU II production Sungai Pakning. The aim of this topic is to calculate the efficiency of centrifugal pump performance. To find performance efficiency we can calculate the head x on the section and discharge channels. Pump head is the maximum height the pump can reach to pump against pressure. After processing the data, it can be seen that after calculating the centrifugal pump efficiency, it is around 8% and the factors that influence pump efficiency are pump and motor power where pump power is influenced by the total head value, flow rate and fluid density. Motor power is influenced by voltage and electric current.